Rekonstruksi Otonomi Khusus Papua melalui Model Strategi Penta Helix Counterinsurgency (COIN): The Implementation of Penta Helix Counterinsurgency (COIN) Strategic Model in Reconstructing Special Autonomy for Papua - MHD Halkis (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
The issues of Papua (Both Papua and West Papua Provinces) have been reached by international communities even though the government regulation; Law of the Republic of Indonesia Number 21, Year 2001, concerning Special Autonomy for Papua Province becoming a central issue as a problem solving to make a special treat for people in Papua internally. Whereas, the regulation is expected to make people in Papua develop political, economic, and cultural also resolving the insurgency problems among them. The arrangements of social and political, economy and budget are as a special treatment, only develop economy and infrastructure but it does not solve the conflicts until today. In this case, the Counterinsurgency (COIN) strategic model needs to be implemented following the appropriateness of national policy and the condition in Papua. This research used a content analysis method to reveal the causes of an un-optimal policy in solving the insurgency. Based on the four elements of COIN, only two elements exist; community and state elements. While the international community element and private sectors do not appear on the special autonomy legislation for Papua. As a reason, the COIN model appropriates with the condition of the people that include some elements; government, local community, the non-state, international community, and private sectors. Comparing to the United States of America (USA) model where the community is not included in the COIN element since the community as an object. On the other hand, it is different from China where military and political parties as important elements since the government decisions are supported by military force to solve the insurgency problem. This research found that civil and military cooperation in the model of COIN Papua after special autonomy is reflected by the existence of Local Government Leaders Communication Forum of Papua to face all situations that happened in Papua, both in security and emergency. Active coordination among governors, local legislators, Adat communities (customary), police, and army for COIN strategy needs special coordination to global communities openly that affect opinions on the people and private sector interests in Papua.